Damage Stability Behavior Analysis of a Cruise Liner Using Computer-Aided Design (CAD) - Nitonye Samson; Feniobu Chris Feniobu; Onyeagba Chukwukamagoi Whizfreeman (International Journal of Marine Engineering Innovation and Research, 2021)
The paper uses more recent scientific and regulatory developments on the damage stability of ships to analyze damage stability of a vessel. The use of CAD in the analysis of several bulky and complex problems facing the maritime sector with respect to ship design and construction has helped reduce human error while more efforts are still made which will possibly eradicate these errors and ensure efficiency in the design and construction of ships. Some softwares are available in the market to support this analysis, as this paper searches to expose the effect on the design and the positive impact on design CAD can if properly integrated into the industry, to this end we used an already existing model of the vessel, made a model of it using the Bentley MaxSurf and then made floodable length analysis using various bulkheads at the fore, aft, and midship region. Thus, generating the graph of floodable length and the various allowable floodable length parameters at different stations.